ADHD, Stress, and Development - Bob, Petr (SpringerBriefs in Psychology,, 2018)
This first-of-its-kind volume revisits current findings on ADHD in terms of classic thinking on developmental neuropsychology for a more rounded concept of brain disorganization. Insights from Freud, Janet, John Hughlings Jackson, and other pioneers help identify mechanisms (e.g., the primitive reflexes) that can cause children with ADHD to be prone to cognitive dissociation when exposed to stressful environments. The authors' model of the developing distracted brain pinpoints effects of stress on cognitive and affective functions, most notably attention and memory, and suggests situations in which stimuli may facilitate integration between brain and mind. This expanded knowledge opens out new educational possibilities for vulnerable students as well as new opportunities for therapeutic breakthroughs for children with ADHD. Included in the coverage: · Definition, diagnosis, and epidemiology of Attention Deficit and Hyperactivity Disorder. · Historical and recent research on ADHD. · Attentional functions, executive dysfunctions, and stress, implications for ADHD. · Neural dissolution, dissociation, and stress in ADHD. · Attention, brain-mind integration and ADHD. · Implications for education and therapy of ADHD children. ADHD, Stress, and Development ably synthesizes past and current understanding into a robust framework with implications for real-world practice. It offers practitioners and researchers new perspectives and future directions in neuropsychology, psychiatry, child and school psychology, and pediatrics.